Perancangan dan Pembuatan Sistem Kearsipan Elektronik Dokumen Proses Bisnis Berbasis Microsoft Access - Rahma Yunita Pratiwi; Mukaram (Records Management System Journal, 2023)
Document archiving is something that is often done by every company, one of which is PT Nusantara Turbine and Propulsion. Document archiving at PT Nusantara Turbine and Propulsion, especially in the Aero Engines Sales and Trading Division, still uses conventional systems. Therefore, the process of searching for documents can take quite a long time. In addition, there is a case experienced by secretaries, namely the loss of archives. This loss of archives is caused by borrowing archives. To overcome this problem, an electronic archive system was created that can store and display information about archives. The system can also record the data of the person who borrowed the archive. In this case, the application that supports the process of designing and creating the system is Microsoft Access. System design and creation can be started from DFD Level 0 and Level 1 and ERD design. As for the creation is done in Microsoft Access which starts from creating tables, forms, reports to queries. The results of the project are the front page, login form, main menu, data input menu, report menu and document search. All features that have been made are tested to the secretary as a user of SAEDPB. The results of the trial were declared acceptable because there were no obstacles when operating. With the search feature and storage of documents in the form of soft files, it is expected to help secretaries in rediscovering archives easily and quickly. This is supported by several studies that say that electronic records management can make it easier for someone when archiving and rediscovering archives. Therefore, the use of SAEDPB is expected to make work more effective and efficient, especially in archiving.